Principios justificativos de la reforma educativa: su concreción en Cataluña - Jaume SARRAMONA (Ediciones Universidad de Salamanca, 2016)
The effective Reformation in the system educational Spanish has in the Organic Law of General Ordination of the Educational System (1990) its fundamental legal base. This Reformation has supposed a general reordering of the system, prolonging the common obligatory schooling for all the students until the 16 years.   The principles that govern the Reformation can group in the following chapters: autonomy, attention to the new social and economic times, systemic conception of the education and answer to the society democratic present and future. To give answer this last point, the Reformation worries about the social participation in the system, of non discrimination, of the attention of the students with difficulties and of the equality of opportunities.   The Reformation has also been an opportunity to modernize the psychological and pedagogic principles that govern the school curriculum, which is shown open and flexible, to assist the diversity of territories and centers of the group of the State.   The transfer of the educational system to the governments of the respective Autonomous Communities makes that variations take place among the diverse territories of the State, according to the own cultural and linguistic necessities, as well as the importance that the same governments and the society in general want to grant to its education. They stay some common basic norms for all.